Depression and diabetic retinopathy: an underexplored connection - Jingwen Li; Hao Sun; Ling Li; Xuelin Xin; Xiao Zhang; Weihong Lv; Shanjuan Tan (Frontiers in Nutrition)
BackgroundDiabetic retinopathy, a major microvascular complication of diabetes, significantly contributes to global blindness. Emerging evidence suggests a potential association between depression and DR, yet the mechanisms remain unclear.ObjectivesThis study aimed to investigate the relationship between depression and DR using nationally representative data from the National Health and Nutrition Examination Survey (NHANES, 2011–2020).MethodsDepression was assessed using the PHQ-9, and DR was identified through self-reported diagnoses. Multivariable logistic regression and restricted cubic splines analyzed the relationship, adjusting for demographic and clinical covariates. Subgroup analyses examined interactions with factors like age and lipid control.ResultsAmong 1,653 participants, the weighted DR prevalence was 18.91%. Depression was independently associated with higher DR risk (OR: 1.69, 95% CI: 1.08–2.64, p < 0.05), with a significant linear relationship between PHQ-9 scores and DR (p < 0.01). Subgroup analyses highlighted stronger associations in older adults and those with well-controlled lipids.ConclusionDepression is a significant and independent risk factor for DR, emphasizing the need for integrated management of mental health and metabolic control in diabetic patients. Addressing depression may reduce DR burden and improve overall quality of life.